Βιβλιοκρισία:M. STEWART, Masculinity, identity, and power politics in the age of Justinian: a study of Procopius [Social worlds of Late Antiquity and the early Middle Ages, 4], Amsterdam: Amsterdam University Press, 2020 - ΚΑΡΔΑΡΑΣ ΓΙΩΡΓΟΣ (Byzantina Symmeikta, 2021)
M. Stewart, Masculinity, identity, and power politics in the age of Justinian: a study of Procopius [Social worlds of Late Antiquity and the early Middle Ages, 4], Amsterdam: Amsterdam University Press, 2020, σελ. 246. ISBN 9789462988231